An age-and sex-matched postoperative therapy should be required in thyroid papillary carcinoma - Yan, Caigu; Sun, Jinjin; He, Xianghui; Jia, Lanning (Frontiers in Endocrinology, 2024)
Background and purpose: Thyroid papillary carcinoma (PTC) had a high possibility of recurrence after surgery, and thyroid stimulating hormone (TSH) suppression and radioactive iodine ( 131 I) were used for postoperative therapy. This study explored the potential mechanism of lymph node metastasis (LNM) and aimed to develop differentiated treatments for PTC.Method: This study explored the risk factors of lymph node metastasis in PTC by analyzing the clinical information of 2073 cases. The Cancer Genome Atlas Thyroid Cancer (TCGA-THCA) and the Gene Expression Omnibus (GEO) databases of gene expression were analyzed to identify the interrelationships between gene expression to phenotype.Results: Analyzing clinical data, we found that male gender, younger age, larger tumor size, and extra-thyroidal extension (ETE) were risk significant risk factors for lymph node metastasis(P<0.05). Conversely, thyroid function parameters such as TSH, FT3, FT4, TSH/FT3, and TSH/FT4 didn't correlate with LNM(P>0.05), and TSH levels were observed to be higher in females(P<0.05). Gene expression analysis revealed that SLC5A5 was down-regulated in males, younger individuals, and those with lymph node metastasis, and a lower level of SLC5A5 was associated with a worse disease-free survival(P<0.05). Additionally, our examination of single-cell RNA sequencing (scRNA-seq) data indicated that SLC5A5 expression was reduced in tumors and lymph node metastasis samples, correlating positively with the expression of TSHR.The impact of TSH on PTC behavior remained unclear, while the capacity for absorbing 131 I in dependence on SLC5A5 showed variations across different genders and ages. We conclude that postoperative treatment of PTC should